A new fractional-order sliding mode controller via a nonlinear disturbance observer for a class of dynamical systems with mismatched disturbances. (July 2016) - Pashaei, Shabnam; Badamchizadeh, Mohammadali
Abstract: This paper investigates the stabilization and disturbance rejection for a class of fractional-order nonlinear dynamical systems with mismatched disturbances. To fulfill this purpose a new fractional-order sliding mode control (FOSMC) based on a nonlinear disturbance observer is proposed. In order to design the suitable fractional-order sliding mode controller, a proper switching surface is introduced. Afterward, by using the sliding mode theory and Lyapunov stability theory, a robust fractional-order control law via a nonlinear disturbance observer is proposed to assure the existence of the sliding motion in finite time. The proposed fractional-order sliding mode controller exposes better control performance, ensures fast and robust stability of the closed-loop system, eliminates the disturbances and diminishes the chattering problem. Finally, the effectiveness of the proposed fractional-order controller is depicted via numerical simulation results of practical example and is compared with some other controllers. Highlights: In this study, a new fractional-order sliding mode controller based on disturbance observer is designed. The finite time stability and mismatched disturbance rejection for a class of fractional-order nonlinear systems is investigated. The finite time and robust stability of closed loop systems is proved via fractional calculus and Lyapunov stability theory. Simulation results with some comparisons demonstrate the effectiveness of the proposed method.